PENGARUH STRUKTUR MODAL, PROFITABILITAS, DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN - Arum Vivian Marfu'ana; Yuli Chomsatu (Jurnal Akuntansi dan Keuangan, 2022)
Companies with resources that affect capital and debt. Capital structure is very important for the sustainability of a company. The purpose of this study is to analyze the factors that affect the firm value of a company. The population in this study are Manufacturing Companies in the Multi-Industrial Sector listed on the IDX in 2019-2020. Sampling in this study using purposive sampling. The sample companies in this study were 15 companies that met the sampling criteria. The data analysis technique uses multiple linear analysis. The results of this study indicate that the capital structure, profitability, and liquidity have an effect on firm value. The results of hypothesis testing indicate that capital structure and profitability have no effect on firm value, while based on the results of hypothesis testing, it shows that liquidity has an effect on firm value.